Exploring equity in audit and feedback trials: Secondary analysis of a systematic review - Zeenat Ladak; Camille Williams; Tolulope Ojo; Camille Renee; Aranee Senthilmurugan; Thomas A. Willis; Victor C. Rentes; Armaghan Dabbagh; Heather A. Shepherd; Tasneem Khan; Janyce Gnanvi; Mary Carter; et al. (PLoS ONE, 2026)
Background One potential approach to eliminating or reducing health inequities for health systems is audit and feedback (A&F). A&F involves providing measurements of quality indicators to health professionals to support continuous quality improvement, and to increase clinicians’ adherence to clinical practice guidelines. In theory, A&F could help direct efforts toward equity deserving sub-groups (e.g., gender-diverse individuals or those living with low-income) by highlighting factors that may place such sub-groups at higher risk of poor health outcomes. In cases where healthcare professionals can make adjustments to their practice or advocate for mitigating supports or services, A&F – when applied broadly – could help to address some health inequities. However, it is unknown whether and how A&F interventions are currently being used to support equity-oriented quality improvement. In this study, we sought to examine the extent to which trials evaluating A&F interventions address health equity. Methods We conducted a secondary analysis of randomized controlled trials included in the latest Cochrane systematic review on the effects of A&F on professional practice, which included articles published up to 2020. We used the PROGRESS-Plus framework to consider the extent to which variables related to equity were examined in the trials. Based on extracted data, studies were categorized as not equity-oriented, equity-informed, or equity-focused. Results Of the 271 articles included within this analysis, 44% of trials were classified as not equity-oriented (n = 120), 35% as equity-informed (n = 95), and 21% as equity-focused (n = 56). The proportion of equity-focused and informed trials increased over the timeline assessed. Only two articles described an equity-oriented framework approach. Only three articles explicitly reported how equity was embedded in their A&F process by highlighting factors including age, gender/sex, and substance use as part of the patient data presented in their feedback. The PROGRESS-Plus factors most commonly considered in the methods or analysis of the trials were age, insurance status, place of residence, and gender/sex. Conclusions A&F trials rarely examine or report the extent to which equity issues inform trial design, A&F processes, analyses, and/or interpretations. Our findings suggest a need for future A&F trials that test explicit approaches to incorporating equity-related interventions to address health equity by helping healthcare professionals, teams, and organizations to be more aware of inappropriate discrepancies in care.